PREVENTION AND MONITORING OF CARDIOVASCULAR COMPLICATIONS IN PATIENTS WITH LUMINAL HER2-NEGATIVE METASTATIC BREAST CANCER - N. A. Kozyavin; T. Yu. Semiglazova (ABV-press, 2018)
Myocardial dysfunction, heart failure and prolongation of the QTc interval are dangerous cardiovascular complications associated with systemic treatment for luminal HER2-negative metastatic breast cancer. Special monitoring is required to control such complications, especially when introducing new drugs. Understanding the mechanisms underlying the development of cardiovascular complications as well as diagnostic, prevention, and treatment strategies is important for optimal patient management.